2018
DOI: 10.1371/journal.ppat.1007003
|View full text |Cite
|
Sign up to set email alerts
|

Loss of CXCR6 coreceptor usage characterizes pathogenic lentiviruses

Abstract: Pandemic HIV-1 originated from the cross-species transmission of SIVcpz, which infects chimpanzees, while SIVcpz itself emerged following the cross-species transmission and recombination of monkey SIVs, with env contributed by the SIVgsn/mus/mon lineage that infects greater spot-nosed, mustached and mona monkeys. SIVcpz and HIV-1 are pathogenic in their respective hosts, while the phenotype of their SIVgsn/mus/mon ancestors is unknown. However, two well-studied SIV infected natural hosts, sooty mangabeys (SMs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 80 publications
0
17
0
2
Order By: Relevance
“…HIV/SIV coreceptor CCR5 expression on the surfaces of naive CD4 ϩ T cells is very low, and viral entry could involve alternative coreceptors, such as CXCR4 in humans or CXCR6 and GPR15 in monkeys (39,40). However, both SIV mac251 , used in this study, and SIV mac239 have been shown to exclusively use CCR5 for entry into rhesus macaque CD4 ϩ T cells (41,42). The lymphoid tissue microenvironment may also have an important role in HIV infection of naive T cells, with increased susceptibility to infection in tonsil lymphoid tissue compared to purified CD4 ϩ T cells alone (43,44).…”
Section: Discussionmentioning
confidence: 91%
“…HIV/SIV coreceptor CCR5 expression on the surfaces of naive CD4 ϩ T cells is very low, and viral entry could involve alternative coreceptors, such as CXCR4 in humans or CXCR6 and GPR15 in monkeys (39,40). However, both SIV mac251 , used in this study, and SIV mac239 have been shown to exclusively use CCR5 for entry into rhesus macaque CD4 ϩ T cells (41,42). The lymphoid tissue microenvironment may also have an important role in HIV infection of naive T cells, with increased susceptibility to infection in tonsil lymphoid tissue compared to purified CD4 ϩ T cells alone (43,44).…”
Section: Discussionmentioning
confidence: 91%
“…We reasoned that genes reported to play putative roles in disease nonprogression of natural hosts would be present in this set of genes. Indeed, CXCR6, the preferred coreceptor of SIV agm that is thought to divert replication from more stem-like CD4 + CCR5 + central memory cells ( 20 , 21 ), was uniquely upregulated in CFSE – CD4 – cells of AGMs and patas monkeys and yet not in rhesus CFSE – CD4 + cells ( Figure 1D ). Importantly, CD4 was one of the most significant DEGs that was unique to CFSE – CD4 + cells ( Figure 1D ), as African green and patas (but not rhesus) CD4 + T cells exhibited significant loss of CD4 transcription in CFSE – CD4 – cells ( Figure 1E ).…”
Section: Resultsmentioning
confidence: 99%
“…Les monocytes ainsi que des sous-populations de lymphocytes T CD4 + au reposnaïfs TN (T naive), à mémoire centrale TCM, à mémoire transitionnelle TTM, et à mémoire effectrice TEM (T effector memory) (Figure 2), et nous avons pu confirmer cette différence en analysant l'expression de la protéine CXCR6 par cytométrie en flux ( Figure 3A). Comme il a été récemment montré que l'utilisation du CXCR6 caractérise l'infection par les lentivirus non pathogènes [9] et qu'elle est abrogée par la présence d'une proline en position 326 de la boucle V3 de la glycoprotéine d'enveloppe gp105, nous avons examiné les 259 séquences de gp105 du VIH-2 dont nous disposions pour la cohorte ANRS-VIH-2, mais aucune de ces séquences ne comportait une proline à cette position. L'analyse transcriptomique a également montré que le gène TRIM5a était plus exprimé dans les TCM que dans les TTM (Figure 2), mais l'analyse de l'expression de la protéine par cytométrie en flux n'a pas permis de confirmer cette différence ( Figure 3B).…”
Section: Distribution Préférentielle Du Réservoir Du Vih-2 Dans Les Lunclassified
“…De plus, le VIH-2, qui utilise les mêmes co-récepteurs CCR5 (C-C chemokine receptor 5) et CXCR4 (c-x-c chemokine receptor 4) que le VIH-1 pour infecter les cellules [6], semble utiliser un plus large spectre de co-récepteurs alternatifs (CCR1 à CCR8, CXCR6, GPR15 [G protein-coupled receptor 15], GPR1, APJ [putative receptor protein related to AT1], CX3CR1 (V28), CXCR5 et RDC1/ CXCR7) in vitro [7]. CXCR6 pourrait être un des co-récepteurs alternatifs majeur du VIH-2 car il serait préférentiellement utilisé chez les patients avirémiques infectés par le VIH-2 [8] ainsi que dans les infections par les lentivirus simiens non pathogènes [9]. Comme pour le VIH-1, l'infection par le VIH-2 semble aboutir à la constitution d'un réservoir de cellules infectées.…”
unclassified